1994
DOI: 10.1143/jjap.33.l715
|View full text |Cite
|
Sign up to set email alerts
|

Flux Pinning in Melt-Grown NdBa2Cu3Oy and SmBa2Cu3Oy Superconductors

Abstract: REBa2Cu3O y superconductors with rare earth (RE) ions with large radii (RE: La, Nd, Sm) exhibit relatively low T c due to the presence of RE-Ba solid solution. We have found that this solid solution can be suppressed if these superconductors are melt processed in a reduced oxygen atmosphere. We have also found that critical current densities of these superconductors are higher than those of melt processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
160
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 429 publications
(164 citation statements)
references
References 8 publications
3
160
0
1
Order By: Relevance
“…The results of experiments on the determination of the calorimetric reaction enthalpies [reactions (1)- (5)] are shown in Tables 1 and 2, where the values of enthalpies are the average of five measurements. The uncertainties quoted in this work refer to a 95 % confidence limit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of experiments on the determination of the calorimetric reaction enthalpies [reactions (1)- (5)] are shown in Tables 1 and 2, where the values of enthalpies are the average of five measurements. The uncertainties quoted in this work refer to a 95 % confidence limit.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Among such compounds, NdBa 2 Cu 3 O y (Nd-123) is the most promising because of its high superconducting transition temperature and enhanced critical current density. [5][6][7] Contrary to YBa 2 Cu 3 O y (Y-123), the Nd 1+x Ba 2-x Cu 3 O y phase reveals a region of homogeneity, and the superconducting properties of the material deteriorate sharply when barium is replaced by neodymium. [8] The region of homogeneity stretches from x = 0 to x = 1 in the Nd 1+x Ba 2-x Cu 3 O y solid solution.…”
Section: Introductionmentioning
confidence: 98%
“…As amostras de SBCO possuem temperatura crítica (T c ) maior que a do YBCO [1,2] e uma solubilidade maior do íon terra rara que no solvente Ba-Cu-O [3], fazendo com que o processo de crescimento seja mais rápido.…”
Section: Introductionunclassified
“…It is clearly shown that the OCMG (oxygen controlled melt growth) NdBaCuO exhibits a higher irreversibility field and an irreversibility temperature, and that it usually shows improved critical current characteristics at higher fields due to the peak effect in the magnetization curve [1,2]. In addition, the growth rate of NdBaCuO is faster than YBCO [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As in YBCO, an oxygen-uptaking process at low temperatures is necessary for good performance. Murakami et al [1,2] observed that, different from MTG YBCO, the oxygen-uptaking at 300-250 C could still strongly improve the superconducting properties for OCMG NdBaCuO. Erb et al [5] also found that the oxygenation temperature, at which the maximum transition temperature can be obtained, is lower for NdBCO than that for YBCO.…”
Section: Introductionmentioning
confidence: 99%